J/ 93-86 : A PROMISING EARLY BULKING POTATO HYBRID FOR GUJARAT - Patel, N. H.; Patel, R. N.; Pandey, S. K.; Kanbi, V H.; Vihol, K. J.; Patel, C. K. (Potato Journal, 2013)
Gujarat state has a very short cool growing period during winter. Potato is normally harvested by mid February to last week of March. Potato growers often face the problem of glut and lower market prices mainly due to bulk arrival of potatoes from most of the states during this peak arrival period. To circumvent this situation some farmers are growing early crop of potato (75 days crop duration) and sell it before normal harvesting season to fetch premium prices. Seven advanced hybrids and three varieties released by CPRI, Shimla were evaluated in randomized block design with six replications at Potato Research Station, Sardarkrushinagar Dantiwada Agricultural University, Deesa, during rabi seasons of 2003-04 and 2004-05. Hybrid J/93-86 gave significantly higher total(200.78 q/ha) and marketable tuber yield (187.80 q/ha) followed by cv. Kufri Ashoka (174.33 q/ha) and cv. Kufri Pukhraj (143.26 q/ha) at 60 days after planting (DAP). It gave 15.17% higher total tuber yield than best control cv. Kufri Ashoka and 31.09% higher marketable yield over best control cv. Kufri Pukhraj. For 75 days harvest, hybrid J/93-86 recorded significantly higher total tuber yield (427.96 q/ha) followed by cv. Kufri Pukhraj (382.24 q/ha). Similar trend for marketable tuber yield was also observed. This hybrid gave 11.96% and 16.62% higher total and marketable tuber yields, respectively than best check cv. Kufri Pukhraj. Hybrid J/93-86 registered highest per cent marketable yield both at 60 and 75 DAP. Keeping the state potato requirement in view, hybrid J/93-86 was found suitable for early harvest and showed potential to replace the popular variety of the region cv. Kufri Pukhraj and it would also be remunerative to the farmers.